ANALISIS IMPLEMENTASI MODEL PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA - Marisa Nurrubi, Hentty; Abdul Latip; Dudung Abdurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
A learning model is a design created to be used by teachers when teaching and learning activities take place. The purpose of writing this article is to describe the literature on the results of the analysis of the implementation of the science learning model on students' creative thinking skills. A total of 30 articles published from 2014-2024 underwent a literature review with 5 stages of literature review, namely selecting the research focus, searching for articles via Google Scholar, selecting articles, carrying out analysis, and organizing written work. The results of the literature study and analysis show 1) Models that can be applied in science learning and as an effort to develop students' creative thinking skills, namely RADEC, cooperative, PBL, DL, BARITO, PjBL, PjBL-STEM, PjBL-Problem solving, inquiry, prediction -observe-explain, CTL (Contexual Teaching and Learning), QL (Quantum Learning), OPPEMEI, creativity learning, mind mapping, creativity problem solving, creativity problem solving combined with mind mapping, science learning model integrated with ethnoscience, STEM-based science learning model, and generative. 2) The learning model applied in science learning has an impact on developing students' creative thinking skills. Through this research, we hope that it can become a reference for implementing learning models in science subjects.